Social alienation in patients with inflammatory bowel diseases: A latent profile analysis - Qingyu Wang; Junyi Gu; Zheng Lin; Sha Li; Meijing Zhou; Jiefeng Yang; Hantian Cheng; Jiali Chen; Yang Lei (International Journal of Nursing Sciences, 2025)
Objectives: The study aimed to explore social alienation types in patients with inflammatory bowel diseases (IBD) and identify influencing factors. Methods: This cross-sectional study was conducted using purposive sampling among patients with IBD from July 2022 to July 2023. Patients were assessed using the Generalized Social Alienation Scale (GSAS), the Brief Illness Perception Questionnaire (B-IPQ), the Hospital Anxiety and Depression Scale (HADS), and the Medical Coping Modes Questionnaire (MCMQ). Demographic and disease-related characteristics were also collected. Latent profile analysis (LPA) was used to identify potential subgroups of social alienation. Univariate analysis and multicollinearity analysis were conducted to explore the influencing factors, followed by multiple regression analysis to evaluate the effect of influencing factors on social alienation. Results: Three distinct profiles of social alienation were identified: integrated-low alienation group (n = 61, 20.20 %), accommodative-moderate alienation group (n = 195, 64.57 %), and maladaptive-high alienation group (n = 46, 15.23 %). Seven characteristics were associated with the profile’s membership: self-perceived financial stress, malnutrition risk, disease duration, illness comprehensibility, anxiety, depression, and acceptance-resignation coping mode. Conclusions: Patients with IBD were categorized into three subgroups based on social alienation levels. Financial stress, malnutrition risk, disease duration, illness comprehensibility, anxiety, depression, and acceptance-resignation coping mode were key predictors of the subgroup membership. Targeted interventions should be developed to mitigate the negative effects of social alienation, with a focus on improving illness perception, alleviating anxiety and depression, and promoting effective coping strategies.